2015
DOI: 10.4103/0970-9371.160559
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and cytotoxic effects of X-ray on buccal epithelial cells following panoramic radiography: A pediatric study

Abstract: Background:Ionizing radiation is a potent mutagenic agent capable of inducing both mutation and chromosomal aberrations. Non-lethal doses of ionizing radiation may induce genomic instability favoring carcinogenesis. In spite of their mutagenic potential, this kind of radiation is an important tool for diagnosis of the disease and is used in medical and dental practice. It has been believed that the number of micronucleus and increased frequency of other nuclear alterations, including karyorrhexis, condensed ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These studies, however, all reported increases in other nuclear alterations (e.g. pyknosis, karyorrhexis and karyolysis) that are associated with increased cytotoxicity [63][64][65][66] . Recently, Preethi et al (2016) reported significant increases in the number of micronucleated cells in BMCs after dental radiography in paediatric patients 62 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies, however, all reported increases in other nuclear alterations (e.g. pyknosis, karyorrhexis and karyolysis) that are associated with increased cytotoxicity [63][64][65][66] . Recently, Preethi et al (2016) reported significant increases in the number of micronucleated cells in BMCs after dental radiography in paediatric patients 62 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, our group recently showed that low doses associated with CBCT examinations are capable of inducing DNA DSBs in vitro in dental stem cells 61 . BMCs have also been used successfully as a biomarker for genotoxic effects, including using the γH2AX assay to detect radiation-induced DNA DSBs 48,62,63 . These studies report increase of genotoxic effects in BMCs after low dose IR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of released monomers is detectable and toxic in vitro, it has been concluded that it is still too small to cause long-term in vivo damage ( 23 ). The analysis of changes in the nucleus within the same period confirmed our hypothesis that there is no difference in genotoxicity between different fissure sealants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being one of the most important agents for remineralization process, fluoride has potentially genotoxic effect ( 24 , 25 ). In addition, the other variables that potentially affect the occurrence of nuclear abnormalities such as gender, age, X-rays exposures medicines intake, the consumption of meat, sweets, soda drinks and tea were analyzed ( 23 , 26 , 27 ). Previous studies have confirmed that age is a variable that affects the genetic content ( 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The micronucleus score obtained in the current study; the pre-exposure values were having a mean ± standard deviation = 4.58 ± 1.8, which was consistent with controls who were not exposed to any genotoxins in Indian population. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%